2012
DOI: 10.1071/wf11079
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of wildfire size and risk changes due to fuels treatments

Abstract: Abstract. Human land use practices, altered climates, and shifting forest and fire management policies have increased the frequency of large wildfires several-fold. Mitigation of potential fire behaviour and fire severity have increasingly been attempted through pre-fire alteration of wildland fuels using mechanical treatments and prescribed fires. Despite annual treatment of more than a million hectares of land, quantitative assessments of the effectiveness of existing fuel treatments at reducing the size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 30 publications
4
91
0
Order By: Relevance
“…2013). Multiple simulations were run (10 simulations at 10 m resolution) to analyze the agreement between observed and simulated perimeters, since the predicted burned area changes from simulation to simulation due to the stochastic behavior caused by spot fires in any run (Cochrane et al 2012), although all input data and parameters were kept constant (Fig. 5).…”
Section: Wildfire Simulationsmentioning
confidence: 99%
“…2013). Multiple simulations were run (10 simulations at 10 m resolution) to analyze the agreement between observed and simulated perimeters, since the predicted burned area changes from simulation to simulation due to the stochastic behavior caused by spot fires in any run (Cochrane et al 2012), although all input data and parameters were kept constant (Fig. 5).…”
Section: Wildfire Simulationsmentioning
confidence: 99%
“…As highlighted by the current and other previous works (Stratton, 2009;Cochrane et al, 2012), FARSITE results in an accurate and reliable single fire event simulator able to replicate observed wildfires at high resolution (20 m or finer resolutions). However, although FARSITE was also applied at landscape scale for several fire modeling and fire likelihood analysis (Bar Massada et al, 2011), other simulators like FlamMap and its command line Randig (also based on Rothermel's fire spread model; Finney et al, 2006) present some advantages with respect to FARSITE when working at large scales (thousands of hectares and square kilometers) and with a huge number of fire ignitions (several thousands for fire modeling) (Ager et al, 2007.…”
Section: Discussionmentioning
confidence: 59%
“…The simulator, which is a semi-empirical model based on Rothermel's (1972) surface fire spread model, simulates fire growth using Huygens's principle wave propagation and fire intensity using Byram's (1959) equation. FARSITE has been widely calibrated in the US and employed not only to generate spatial maps of fire spread and behavior (Finney and Ryan, 1995;Finney, 1998) but also to evaluate the effects of different silvicultural prescriptions and fuel treatment options on reducing fire hazard (Stephens, 1998;Finney, 2001;Stratton, 2004;LaCroix et al, 2006;Ryu et al, 2007;Schmidt et al, 2008;Cochrane et al, 2012). The use of FAR-SITE simulator on areas different from those ones where the model was originally developed requires a local calibration and validation (Arca et al, 2007) using observed wildfire data and is the primary step to applying the simulator at larger scales (Ager et al, 2007;Stratton, 2006;Salis et al, 2013).…”
Section: R Jahdi Et Al: Calibration Of Farsite Simulator In Northermentioning
confidence: 99%
“…Numerous recent fires in the western U.S. have been managed in part or in whole for ecological benefit (henceforth "restoration fires"), including over 12 fires in 2017 totaling more than 60,000 ha of burned area (Forest Service Fire and Aviation Management, personal communication). Both modeling and empirical studies support these actions by showing that wild and prescribed fires can limit growth and lower severity of future fires and losses (Collins et al 2009, Arkle et al 2012, North et al 2012, Houtman et al 2013, Hoff et al 2014, Parks et al 2014, 2015a, Price et al 2015 and facilitate suppression efforts (Moghaddas and Craggs 2007, Syphard et al 2011b, Cochrane et al 2012, Thompson et al 2016. However, despite these and other studies, including landscape simulation research in which alternative fire management studies are simulated over time Mladenoff 2007, Spies et al 2014), research is nonexistent on how landscape fire regimes and suppression budgets might change following long-term changes in fire policy.…”
Section: Introductionmentioning
confidence: 99%